Plug-in electric vehicles automated charging control - David Dallinger; Robert Kohrs; Michael Mierau; Simon Marwitz; Julius Wesche (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2015)
This paper examines how plug-in electric vehicles can be managed to balance the fluctuation of renewable electricity sources. In this context, different control strategies are introduced. To investigate indirect control via electricity tariffs, an electricity market analysis is conducted of a system with a high share of generation from renewable electricity sources. The analysis uses driving data collected from battery electric and plug-in hybrid vehicles in a research project which means that real charging and driving behavior can be considered. The results show that it is difficult to implement smart charging based on economic arguments because the incentives from day-ahead electricity markets are relatively small. In addition, a novel, autonomous control approach is discussed for plug-in electric vehicles. While measuring the voltage at the grid connection point, plug-in electric vehicles are able to fully independently generate operation schedules that can avoid load peaks and integrate fluctuating power outputs from distributed renewable generation sources. The results reveal that combining indirect, price-based control to consider the system level with autonomous voltage-based control to consider the situation in distribution grids is a very promising control approach that allows electric vehicles to benefit from sustainable renewable generation and avoids load peaks due to simultaneous charging.
urn:nbn:de:0011-n-3279201
Keywords: 330